MicroRNAs: Potential mediators between particulate matter 2.5 and Th17/Treg immune disorder in primary membranous nephropathy - Zhou, Xiaoshan; Dai, Haoran; Jiang, Hanxue; Rui, Hongliang; Liu, Wenbin; Dong, Zhaocheng; Zhang, Na; Zhao, Qihan; Feng, Zhendong; Hu, Yuehong; Hou, Fanyu; Zheng, Yang; et al. (Frontiers in Pharmacology, 2022)
Primary membranous nephropathy (PMN), is an autoimmune glomerular disease and the main reason of nephrotic syndrome in adults. Studies have confirmed that the incidence of PMN increases yearly and is related to fine air pollutants particulate matter 2.5 (PM2.5) exposure. These imply that PM2.5 may be associated with exposure to PMN-specific autoantigens, such as the M-type receptor for secretory phospholipase A2 (PLA2R1). Emerging evidence indicates that Th17/Treg turns to imbalance under PM2.5 exposure, but the molecular mechanism of this process in PMN has not been elucidated. As an important indicator of immune activity in multiple diseases, Th17/Treg immune balance is sensitive to antigens and cellular microenvironment changes. These immune pathways play an essential role in the disease progression of PMN. Also, microRNAs (miRNAs) are susceptible to external environmental stimulation and play link role between the environment and immunity. The contribution of PM2.5 to PMN may induce Th17/Treg imbalance through miRNAs and then produce epigenetic affection. We summarize the pathways by which PM2.5 interferes with Th17/Treg immune balance and attempt to explore the intermediary roles of miRNAs, with a particular focus on the changes in PMN. Meanwhile, the mechanism of PM2.5 promoting PLA2R1 exposure is discussed. This review aims to clarify the potential mechanism of PM2.5 on the pathogenesis and progression of PMN and provide new insights for the prevention and treatment of the disease.